EVALUASI PERGERAKAN TANGGUL LUMPUR SIDOARJO - Sukandi (JURNAL SANGKAREANG MATARAM, 2015)
The eruption of mud flow in Sidoarjo since 29 th May 2006 still continues and has resulted in the changing of soil condition in the surrounding area. Form handlingof mud flow in this time is to build retaining embankment that surrounds the puddle area, where embankments rest on the alluvium layer. The objectives of this research are evaluate the deformation and stability analysis of embankment were caused by the mud flow. Methods in this research is having study on the secondary and primery data to get input parameter in the calculation. At this simulation used by embankment P10D/KR5 of condition exsisting. The simulation used Plaxis program on the plane strain condition with Mohr-Coulomb model for embankment and soil, while was gabion with its material approached by elastic linear model. The research results show that the embankment stability towards the collapse of bearing capacity is about SF = 2,5. After the mud eruption, there is change on the condition of soil resulting in the embankment settlement about 2,578 m based on the monitoring data real. Theresult of simulation was observed from the settlement and it was accurate enough according to the field measurement. If earthquake load was added to model, it resulted in the increase of vertical displacement about 8.0% on the embankment.The simulation isable to show that being deeper from the soil surface, the horizontal displacement of soil is very significant and there is movement towards the eruption. It is done by modeling of change in the soil layer condition, the closer to the source of mud, the layer condition is getting softer. At the end of filling with condition of eruption, the embankment stability declines drastically intostatic load of 1,103 and dynamic of 1,095.The erosion area tends to cut the embankment body until soil foundation.